An integrated approach of estimating demand response flexibility of domestic laundry appliances based on household heterogeneity and activities. (July 2020) - Yamaguchi, Yohei; Chen, Chien-fei; Shimoda, Yoshiyuki; Yagita, Yoshie; Iwafune, Yumiko; Ishii, Hideo; Hayashi, Yasuhiro
Abstract: Demand response (DR) is widely recognized as an alternative approach to achieving the supply-demand balance of power systems. The accurate quantification of DR flexibility potential is important for implementing DR, especially in countries where fewer DR related studies have been conducted and where the societal structures determining DR flexibility are different from the US and Europe. This study designs an interdisciplinary framework by integrating household characteristics based on population census, activity-based energy demand modeling, and a survey on the behavioral intention to participate in DR and shift energy use. This study quantifies the DR flexibility potential of washing machines and dryers used in 18.9 million households in the Kanto region in Japan with a peak electricity demand of 57 GW. These appliances are estimated to be capable of increasing electricity demand by 70–220 MW, depending on the time of day when DR is activated for 60 min. This potential decreases with the duration of DR. The estimated potential per household is much smaller in Japan than in Europe. The results highlight the importance of promoting DR to the majority of populations, particularly among the underserved populations, and addressing the behavioral and cultural barriers to promoting DR. Highlights: Demand response flexibility potential of domestic laundry appliances was quantified. Multi-faceted factors of household activities and characteristics were considered. Flexibility potential per household was found to be much smaller in Japan than in Europe. Flexibility over 100 MW provided only when majority of population participated.